Answer:
a=-4 and b=6
Explanation:
![(a)/(x-8) +(b)/(x+4) =(2x-64)/((x-8)(x+4))](https://img.qammunity.org/2020/formulas/mathematics/high-school/2sea7nmlnla1ags4dlozclxzm3lwq8iy.png)
First, add the fractions by finding the common denominator.
In this case, (x-8)(x+4).
![(a(x+4) + b(x-8))/((x-8)(x+4)) =(2x-64)/((x-8)(x+4))](https://img.qammunity.org/2020/formulas/mathematics/high-school/utlded9km0xblc08sq924itm6unqzqqlry.png)
Therefore, the numerators are equal:
![a(x+4) + b(x-8) =2x-64](https://img.qammunity.org/2020/formulas/mathematics/high-school/tm9t8awme2lgdt6ajoij7kxv8upbhu0r6t.png)
Simplify:
![ax+4a + bx-8b =2x-64\\(a+b)x+4a-8b=2x-64](https://img.qammunity.org/2020/formulas/mathematics/high-school/pqkiyct84pxnx86ijoda4twlqxea9p507c.png)
Now match the coefficients.
![a+b=2, 4a-8b=-64](https://img.qammunity.org/2020/formulas/mathematics/high-school/15jg6wipnv6wqb3sk690kbtljbai2rjnsf.png)
Solve the system of equations. I'll use substitution, but you can also use elimination if you prefer.
![4a-8b=-64\\a-2b=-16\\(2-b)-2b=-16\\2-3b=-16\\-3b=-18\\b=6\\a=-4](https://img.qammunity.org/2020/formulas/mathematics/high-school/nkj0dfailundklgsdf6erqs2y1wmdngwr2.png)
Therefore, a=-4 and b=6.